Mengembangkan Bahan Ajar Dalam Pembelajaran Ilmu Pengetahuan Sosial (Ips) di Sd - Manurung, Jamson; Haloho, Bongguk; Napitu, Ulung (Lembaga Penelitian dan Pendidikan Mandala, 2023)
Abstract. Learning The world of education continues to experience changes for the better and is increasingly sophisticated, effective and efficient. Therefore, a very important component is needed, one of which is learning material. Learning materials are all the information, tools and texts needed by the teacher/instructor to plan and evaluate the implementation of learning. Teaching materials are a set of tools that contain learning materials, methods, limitations and how to evaluate. Teaching materials can be in the form of written or unwritten things that are used by teachers/instructors and students in the teaching and learning process in the classroom. Learning material is also the knowledge, skills and attitudes that must be learned by students to achieve predetermined competencies. Learning materials consist of knowledge (facts, concepts, principles, procedures), skills, attitudes and values. The problems/obstacles that often occur and are faced by teachers who teach social studies in elementary schools are determining or choosing appropriate teaching materials that can help students achieve these competencies. This is because the curriculum only contains an outline of the basic material. So it is the teacher's obligation to find and describe the basic material in detail so that it becomes a complete learning material that can help teachers and students in the teaching and learning process.Keywords: Learning Materials, Learning of Social Science Abstrak. Dunia pendidikan terus mengalami perubahan kearah yang lebih baik dan semakin canggih, efektif dan efisien. Oleh karena itu di butuhkan komponen yang sangat penting, salah satunya materi pembelajaran. Materi pembelajaran adalah semua informasi, alat dan teks yang diperlukan oleh guru/pengajar untuk merencanakan dan mengevaluasi pelaksanaan pembelajaran. Bahan ajar merupakan seperangkat sarana yang berisi materi pembelajaran, metode, batasan-batasan dan cara mengevaluasi. Bahan ajar dapat berupa hal-hal tertulis maupun tidak tertulis yang digunakan oleh guru/pengajar dan peserta didik dalam proses belajar mengajar di kelas. Materi pembelajaran juga merupakan pengetahuan, keterampilan dan sikap yang harus dipelajari oleh peserta didik untuk mencapai kompetensi yang telah ditentukan. Materi pembelajaran terdiri dari pengetahuan (fakta, konsep, prinsip, prosedur), keterampilan, sikap dan nilai. Masalah /kendala yang sering terjadi dan dihadapi oleh guru yang mengajar IPS di sekolah dasar adalah menentukan atau memilih bahan ajar yang tepat sesuai yang dapat membantu peserta didik mencapai kompetensi tersebut. Hal ini disebabkan karena kurikulum hanya memuat garis besar materi dasar. Maka menjadi kewajiban guru untuk mencari dan menjabarkan materi dasar tersebut secara rinci sehingga menjadi bahan pembelajaran yang utuh yang dapat membantu guru dan peserta didik dalam proses belajar mengajar.Kata Kunci: Materi Pembelajaran, Pembelajaran Ilmu Sosial.